The petroleum system: a new classification scheme based on reservoir qualities - Jing-Zhou Zhao (KeAi Communications Co., Ltd., 2018)
Abstract A new classification of petroleum systems (PSs) based on reservoir qualities is proposed. We classify PSs into the following three basic types: (1) source-rock petroleum system (SPS); (2) tight-reservoir or tight petroleum system (TPS); and (3) conventional-reservoir or conventional petroleum system (CPS). The CPS is a PS in which hydrocarbons accumulate in conventional reservoirs, and all the essential elements and processes are significant and indispensable. Oil and gas accumulations are geographically discrete and therefore exist as discontinuous accumulations. The TPS is a PS where hydrocarbons accumulate in tight reservoirs and the source rock, reservoir, seal, migration, and trap are also indispensable, but the traps are mostly non-anticlinal and the accumulations are primarily quasi-continuous and secondarily discontinuous. The SPS is a PS where both hydrocarbon generation and accumulation occurred in source rocks and traps and migration are unnecessary or inconsequential; the hydrocarbon distribution is extensive and continuous and has no distinct boundaries. The aforementioned three PSs can be derived from a common hydrocarbon source kitchen and are closely linked in terms of their formation and distribution. Therefore, to maximize the exploration efficiency, a comprehensive study and different strategies are needed by considering the SPS, TPS, and CPS as parts of a greater whole.